The interfacial digestion behavior of crystalline oil-in-water emulsions stabilized by sodium caseinate during in vitro gastrointestinal digestion. (September 2022) - Wan, Liting; Li, Lin; Xiao, Jiawei; He, Ni; Zhang, Rixin; Li, Bing; Zhang, Xia
Abstract: The interfacial digestion behavior of crystalline oil-in-water (O/W) emulsions was studied using sodium caseinate-stabilized 4% and 20% palm stearin-in-water emulsions (4% PS and 20% PS) with 4% and 20% palm olein-in-water emulsions as control. Variations in fat crystal form and microstructure, interfacial adsorbed protein percentage and concentration, and rheological properties during in vitro gastrointestinal digestion and intestinal lipid digestion behavior were determined. Initially, fat crystals in both PS-based emulsions were dominated by β′ polymorph. After gastric digestion, the β′-to-β transition was observed and both PS-based emulsions mainly contained β crystals, but 20% PS had a higher β crystal content (∼85% vs. 60%, p < 0.001) and viscosity than 4% PS. These β crystals induced in the gastric phase with large size, dense packing, and a high onset melting temperature (46.8 ± 0.2 °C) probably played a major role in slowing down lipid digestion, as confirmed by a greater extent of decreased lipolysis rate of 20% PS (∼37%) than 4% PS (∼10%) at the initial stage of intestinal digestion. The lipolysis extent of PS-based emulsions is strongly dependent on their solid fat content (SFC). The digestion extent of 4% PS was not affected by its low SFC (2.6%), while a high SFC of 20% PS (12.5%) promoted its lipolysis as fat crystals in it adsorbed at the oil-water interface to facilitate the formation of stable spherical droplets. This study highlighted the crucial role of gastric rather than initial fat crystal polymorph in impacting lipid digestion rate of protein-stabilized O/W emulsions. Graphical abstract: Image 1 Highlights: Gastric digestion induced β′ to β transition in both PS-based emulsions. β′ crystals in initial 20% PS hindered interfacial protein adsorption. The viscosity of PS-based emulsions increased with SFC after in vitro digestion. Spherical droplets formed after intestinal digestion in PS-based emulsions were stabilized by interfacial fat crystals. β crystals formed after gastric digestion significantly suppressed intestinal lipolysis rate.